New method for the onset point determination of the petroleum asphaltene aggregation; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Gorshkov A. M. Anton Mikhailovich (High Technologies in Oil and Gas Development, 2014)
Title screen